2000
DOI: 10.1139/z00-151
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged winter undernutrition and the interpretation of urinary allantoin:creatinine ratios in white-tailed deer

Abstract: The urinary allantoin:creatinine (A:C) ratio (expressed in micromoles of allantoin to micromoles of creatinine) has shown potential as an index of recent winter energy intake in preliminary controlled studies of elk (Cervus elaphus) involving mild condition deterioration (up to 11% loss of body mass). To ensure reliable nutritional assessments of free-ranging cervids by measuring A:C ratios of urine in snow, it is essential to extend this work. We assessed the effect of moderate and severe winter nutritional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Eventually, this female lost 29% of its body mass and recovered with difficulties thereafter. Similar increases in A:C (DelGiudice et al 2000) and M:C (as collected from the urinary bladder; DelGiudice et al 1998) have been shown in white-tailed deer, starting at ca 25% of body mass loss. These observations suggest that phase-III of starvation commences at a loss of ca 20-25% body mass in white-tailed deer.…”
Section: Discussionsupporting
confidence: 62%
“…Eventually, this female lost 29% of its body mass and recovered with difficulties thereafter. Similar increases in A:C (DelGiudice et al 2000) and M:C (as collected from the urinary bladder; DelGiudice et al 1998) have been shown in white-tailed deer, starting at ca 25% of body mass loss. These observations suggest that phase-III of starvation commences at a loss of ca 20-25% body mass in white-tailed deer.…”
Section: Discussionsupporting
confidence: 62%
“…Additionally, all samples with A:C ratios . 1.0 (17 samples or 2.7%) were eliminated because such values appear to violate biological maxima , Delgiudice et al 2000.…”
Section: Dependent Variables: Describing Elk Winter Nutritionmentioning
confidence: 99%
“…The physical toll of morning sickness, gestation, and lactation in humans can also cause increases in ␦ 15 N values (Fuller et al 2005). In addition, sustained physical exertion, disease, injury, or hibernation can result in increased ␦ 15 N values (Delgiudice et al 2000;Habran et al 2010;Lee et al 2012;Rode et al 2016). We use the term nutritional stress here to include events, such as fasting and physical exertion, that surpass replacement of calories and result in catabolism of tissues producing a shift to higher ␦ 15 N values.…”
Section: Introductionmentioning
confidence: 99%